Profiling of miRNAs in neonatal cloned bovines with collapsed lungs and respiratory distress. (8th February 2018) - Zhang, FY; Yang, N; Rao, YF; Du, WH; Hao, HS; Zhao, XM; Zhu, HB; Liu, Y
Contents: Neonatal respiratory distress is a major mortality factor in cloned animals; however, the pathogenesis of this disease has rarely been investigated. Previous studies have shown that miRNAs regulate critical genes related to lung development, cell differentiation, surfactant synthesis, secretion and lung disease. This study aimed to examine differentially expressed miRNAs in collapsed lungs of cloned bovine neonates and normal lungs in order to identify key pathways and functions that might be related to the pathogenesis of neonatal respiratory distress. In this study, miRNA transcriptomes of collapsed lungs of neonatal cloned bovines and normal lungs were analysed by next‐generation sequencing and the results were validated using quantitative real‐time PCR (qRT‐PCR). A total of 177 differentially expressed miRNAs were identified in the two groups (fold change > 2, RPM ≥ 5), some of which were associated with type II cell differentiation, for example, mmu‐miR‐29a‐5p_L‐2R+1, hsa‐miR‐200c‐5p_L‐1R+1 and mmu‐miR‐18a‐3p_R+1. The differentially expressed miRNAs were predicted to 6, 031 target genes. By Gene Ontology (GO) and Kyoto Encyclopeida of Genes and Genomes (KEGG) DATA base, 133 significant GO terms ( p < .05) and 13 significant KEGG pathways ( p < .05) were obtained. Many of them were associated with lung development and surfactant homoeostasis, such as lipid biosynthetic processes, protein transport, endocytosis, lysosome, endosome, Golgi apparatus and membrane. Our results of miRNAs express profiles may partially explain the respiratory distress and lung collapse in neonatal bovine clones and could provide novel insights into roles of miRNAs in regulation of lung collapse and neonatal respiratory distress in cloned farm animals.